2023
DOI: 10.1039/d3ob00904a
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-catalyzed reactivity of carbenes with boronic acid derivatives for arylation (alkylation) and beyond

Akanksha Babbar,
Pokhriyal Yamini,
Mohammad Saleem
et al.

Abstract: This comprehensive review article discussed the reactivity of carbenes with boronic acid derivatives for the one-pot synthesis of diarylmethanes, difluoromethylated arenes, aryl, alkyl boron compounds, arylacetic acid derivatives, furan derivatives,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…4 Later, many groups expanded this chemistry with different transition-metal catalysts under the thermally induced transformation of different carbene sources with boronic acid derivatives. 5 Similarly, Barluenga and Valdés's group reported the reaction of boronic acid derivatives with carbenes, which are derived from N -sulfonylhydrazones. 6 Many groups expanded this chemistry for C–C and C–B bond formations 7 and related compounds 8 with or without using any transition-metal catalyst (Scheme 1a).…”
mentioning
confidence: 97%
“…4 Later, many groups expanded this chemistry with different transition-metal catalysts under the thermally induced transformation of different carbene sources with boronic acid derivatives. 5 Similarly, Barluenga and Valdés's group reported the reaction of boronic acid derivatives with carbenes, which are derived from N -sulfonylhydrazones. 6 Many groups expanded this chemistry for C–C and C–B bond formations 7 and related compounds 8 with or without using any transition-metal catalyst (Scheme 1a).…”
mentioning
confidence: 97%
“…Carbenes are versatile synthetic intermediates in organic chemistry for C–C, C–heteroatom bond formation, etc., and for the construction of different carbocyclic and heterocyclic compounds in a single step. Addition of carbenes including metallo carbenes to NN bonds is a reaction that is scantily addressed in the literature. In 1977, Stang’s group reported that the vinyl carbenes derived from vinyl triflate add to azoarenes to yield 2-indazoles .…”
mentioning
confidence: 99%